Flexible Pedagogy, Flexible Practice: Notes from the Trenches of Distance Education - Elizabeth Burge (Issues in Distance Education, 2011)
Flexibility has become a watchword in modern education, but its implementation is by no means a straightforward matter. Flexible Pedagogy, Flexible Practice sheds light on the often taken-for-granted assumptions that inform daily practice and examines the institutional dynamics that help and hinder efforts towards flexibility. The collection is international in scope, drawing on the experience of specialists in distance education from North America, the United Kingdom, Australia and New Zealand, South Africa, Singapore, and Japan. Contributors to the volume were asked to reflect candidly and critically on questions that include: •What precisely is flexible learning? •Who or what is driving the flexibility agenda, and for whose benefit? And •who or what is resisting it? •What challenges must be overcome in order to achieve flexibility, and what are some of the compromises it can entail? In addressing these and other issues, the authors offer a wealth of theoretical insights and a frank assessment of their practical experience. Their report from the trenches will be invaluable to anyone seeking to broaden the reach of higher education. "Essentially, the book is about what happens when the canonical concept collides with the 'rough terrains of practice,' and in addressing this question, it succeeds admirably. . . . And there's more - much more - from the thirty-three contributors, in addition to the insightful 'wrap-around' provided by the editors. . . . Your thinking will be both challenged and informed." -David Murphy (read the rest of the review at David Murphy's Occasional Blog)